EVALUATION OF PHYTOCHEMICAL AND ANTIBACTERIAL POTENTIAL OF HELICTERES ISORA L. FRUITS AGAINST ENTERIC BACTERIAL PATHOGENS - Tambekar, Dilip H; Khante, B. S.; Panzale, B. K.; Dahikar, S. B.; Banginwar, Y. S. (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
Antibacterial activities of aqueous, acetone, ethanol and methanol extracts of fruits of Helicteres isora (Mororphali) were studied. The fruit aqueous extracts of H. isora showed prominent antibacterial activities against E.coli, Staphylococcus epidermidis, Salmonella typhimurium and Proteus vulgaris; moderate activity against Enterobacter aerogenes, Staphylococcus aureus, Salmonella typhi and least activity against Pseudomonas aeruginosa. The aqueous extract showed maximal, the ethanol and methanol extract moderate and acetone extracts least antibacterial activities. Phytochemical screening revealed the presence of carbohydrates, anthraquinon glycosides, proteins, tannin and phenolic compounds and steroids These antibacterial properties supports its traditional use of fruits of H. isora in the treatment of enteric or diarrhoeal infections.